PENGARUH LATIHAN CIRCUIT TRAINING TERHADAP DAYA TAHAN TIM BULUTANGKIS SMKN 5 PEKANBARU - Gusmulianto '; Slamet '; Ni PutuNita Wijayanti (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2017)
Abstract: Based on the observation of researcher in the field, the badminton players of SMK N 5 Pekanbaru didn’t have good endurance. It can be seen athletes are exhausted quickly in doing the exercises and the competition, so that the exercise is not maximum, not free or athletes move slowly, it’s because of excessive fatigue, so that the movement is not maximum, as well as blow’s given also less than the maximum, so that it could be defeated easily by his opponent. The purpose of this research was to determine the effects of the circuit training for endurance badminton team SMKN 5 Pekanbaru. Population in this research are all badminton players of SMKN 5 Pekanbaru. The numbers of players are 8 people. In this research, sampling techniques to be used is a total sampling, the sampling determination when all members of the population used as a sample, so the sample is 8 people. This research instrument used a Bleep Test. The data obtained were analyzed by using t-test. Based on - t produce t-count of 2,595 to 1,753 t-tabel then accepted, at the level of alpha (0.05 in. It can be concluded that there are significant circuit training for endurance In Badminton team in SMK N 5 Pekanbaru. Keywords: Circuit Training, Endurance